2013
DOI: 10.1007/s00701-013-1797-7
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival oedema as a potential objective sign of intracranial hypertension: a short illustrated review and three case reports

Abstract: Periorbital and conjunctival oedema has been reported anecdotally by patients with raised intracranial pressure states. We present three clinical cases of this phenomenon and discuss the current evidence for pathways by which cerebrospinal fluid (CSF) drains in relation to conjunctival oedema. We reviewed the available literature using PubMed, in regards to conjunctival oedema as it relates to intracranial hypertension, and present the clinical history, radiology and orbital photographs of three cases we have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…There was no evidence of allergy or infection as a cause of conjunctival edema. CSF was previously thought to only drain through the arachnoid villi and granulations, however, recent evidence suggests that CSF drains through other pathways [19]. Koh et al [20] in their review of the literature concluded that the majority of flow of CSF is along the cranial nerves and into extracranial lymphatics.…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of allergy or infection as a cause of conjunctival edema. CSF was previously thought to only drain through the arachnoid villi and granulations, however, recent evidence suggests that CSF drains through other pathways [19]. Koh et al [20] in their review of the literature concluded that the majority of flow of CSF is along the cranial nerves and into extracranial lymphatics.…”
Section: Discussionmentioning
confidence: 99%